The Role of the Depok Metro Police Sabhara Patrol Unit in Reducing the Crime of Theft in Depok City During the Covid-19 Pandemic - Arsyil Mukmin Risalaita Sangadji (Police Studies Review, 2021)
Nowadays, motorized vehicles are an important human need. However, the pandemic situation resulted in the layoff of many people. Thus, the welfare of the community is getting lower, resulting in higher thefts occur. The Sabhara unit is tasked to preventing crime. The problems of this study are: 1. What is the general description of the implementation of patrol units of Depok Police region and the crime rate of motorcycle criminal acts in Depok? 2. How does the role of Sabhara patrol unit in reducing the amount of motorcycle criminal acts in Depok during covid-19 pandemic? 3. What are the factors that influence the implementation of Sabhara patrol units of Depok police to overcome the motorcycle criminal acts in Depok? This study uses qualitative approach. The focus of the study is the role of the patroli unit of the sabhara Depok Police in reducing motorcycle criminal actions in Depok city during Covid-19 pandemic. This study uses primary and secondary data with data collection techniques in the form of interviews, observation, and document review. Triangulation of data is used to validating the data. The patrol activities carried out by the sabhara units are an effort to prevent motorcycle criminal acts. There are two forms of patrol which are four wheels patrol and two wheels patrol. Both patrols are carried out regularly everyday with two schedules and three teams. There are several factors that influence the implementation of patrol which can be linked to the 6M elements of management theory. Suggestions for optimizing patrol activities which are, increasing the human resources, intensify the patrols schedule, renewing the facilities, and socialization to the community.